(untitled) (Plant Tissue Culture and Biotechnology, 2016)
The potential of various culture lines of Atropa acuminata were investigated for resourcing acid phosphatase (ACP) (3.1.3.2). Crude enzyme extract comprised of a mixture of four isoforms, distinguishable by polyacrylamide gel electrophoresis (PAGE) with molecular weight ranging from 39 to 215 kDa. In vitro regenerated proliferative shoots, callus and roots showed higher specific activity (2.49, 3.41, 2.91 U/mg protein, respectively) as compared to in vivo grown plants (0.71 U/mg protein). ACP activity in root cultures increased progressively up to 4.6 U/mg during the entire growth period (2 ? 24 weeks), whereas in case of shoot cultures, the specific activity escalated to 2.49 U/mg at 8 weeks, which then declined subsequently (1.95 U/mg). Similarly, callus cultures initially showed a higher phosphohydrolytic activity (3.41 U/mg protein) until 8 weeks by which period, it decreased with the passage of growth period. The present studies reveal an alternate system for resourcing of ACP from Atropa acuminata. Plant Tissue Cult. & Biotech. 26(1): 15-23, 2016 (June)